Dance anatomy - Haas, Jacqui Greene 1958- (Anatomy series, 2018)
Dance Anatomy is a visually stunning presentation of more than 100 of the most effective dance, movement, and performance exercises, each designed to promote correct alignment, improved placement, proper breathing, and prevention of common injuries.